Diversity in the practice of district ethics committees. Issue 6713 (9th December 1989) - Gilbert, C.; Fulford, K. W.; Parker, C.
Abstract : A survey of ethics committees in district health authorities was carried out to find out the size and make up of committees and what information and guidance they offered to scientists who apply to do research. A sample (n = 28) of committees in England (n = 190), half from teaching districts and half from non-teaching districts, was contacted by post requesting this information. A high degree of diversity was found, not only in the methods that committees used but also in the ethical criteria each considered to be pertinent for research. It was also shown that published guidelines have made little impact. It is suggested that issuing more guidelines will be of limited use. Rather, the following are needed: information about why guidelines have been widely ignored, better communication between committees, some form of education for committee members, and a formal register of committees compiled.